2020
DOI: 10.1039/c9ce01825e
|View full text |Cite
|
Sign up to set email alerts
|

Controllable synthesis of CoFe2O4 electrospun nanofibers

Abstract: Controllable synthesis of CoFe2O4 nanofibers has been realized by controlling the electrospinning process parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…One may note that the intensity of the diffraction peaks of CFO is much weaker than that of the PZT due to the difference in the crystallization temperature for PZT and CFO. It reported that the CFO phase has a higher crystallization temperature than that of the PZT phase, and a weak CFO diffraction peak was observed in CFO‐PZT NFs 2,17 . The morphology of coaxial NFs annealed at 700°C is shown in Figure 1B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One may note that the intensity of the diffraction peaks of CFO is much weaker than that of the PZT due to the difference in the crystallization temperature for PZT and CFO. It reported that the CFO phase has a higher crystallization temperature than that of the PZT phase, and a weak CFO diffraction peak was observed in CFO‐PZT NFs 2,17 . The morphology of coaxial NFs annealed at 700°C is shown in Figure 1B.…”
Section: Resultsmentioning
confidence: 99%
“…It reported that the CFO phase has a higher crystallization temperature than that of the PZT phase, and a weak CFO diffraction peak was observed in CFO-PZT NFs. 2,17 The morphology of coaxial NFs annealed at 700°C is shown in Figure 1B. The NFs show a smooth and bead-free morphology with an average diameter ranging from 150 to 350 nm.…”
Section: Methodsmentioning
confidence: 99%
“…1a illustrates the fabrication procedure of the CFO/PI lm, which was utilized as a exible magnetostrictive substrate for 2-2 type laminated ME composite via electrospinning, calcination, and spin-coating process (see details in the Experimental section). Aer electrospinning, annealing under appropriate conditions 36,37 is necessary to remove amorphous PVP from the as-spun nanobers and obtain well-crystalline CFO nanobers. The XRD patterns of the CFO nanobers synthesized aer calcination are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis details for CFO nanofibers can be found in our previous reports. 3,31 PZT film was deposited on SRO/NFO/mica substrate with CFO nanofibers at 600 • C with an oxygen partial pressure of 15 Pa. After the deposition of PZT, the CFO nanofibers were covered by the PZT film layer, as shown in Figure 1A. Pt electrodes with a diameter of 100 µm were deposited on the surface of these composite films by sputtering.…”
Section: Methodsmentioning
confidence: 99%
“…CFO nanofibers were received on mica substrates with SrRuO 3 (SRO) electrodes buffered with NiFe 2 O 4 (NFO). Synthesis details for CFO nanofibers can be found in our previous reports 3,31 . PZT film was deposited on SRO/NFO/mica substrate with CFO nanofibers at 600°C with an oxygen partial pressure of 15 Pa. After the deposition of PZT, the CFO nanofibers were covered by the PZT film layer, as shown in Figure 1A.…”
Section: Methodsmentioning
confidence: 99%